Determination of Irrigation Water Surface Flow Velocity Using Video Analysis with Tracker Application and Linear Regression - Mahfudz, Khawarizmy; Ishafit, Ishafit (JURNAL PEMBELAJARAN FISIKA, 2025)
Advances in computer technology and software allow for more practical and accurate measurements. This study aims to measure the velocity of irrigation water surface flow using video analysis with Tracker application and linear regression in Microsoft Excel. Video data was recorded in the irrigation canal of Bendhung Lepen, Yogyakarta, using bamboo leaves as test objects. The analysis process involved tracking the motion of the object in the video and calculating the velocity based on the slope of the displacement versus time graph. The results showed that the velocity of water surface flow was (8.39 ± 0.05) cm/s from Tracker analysis and (8.39 ± 0.04) cm/s from Excel linear regression, with a correlation coefficient of 0.9985 and a coefficient of determination of 0.9971. This method proves the reliability and efficiency of a technology-based approach to water velocity measurement.